Developing talent in young people /edited by Benjamin S. Bloom ; contributors, Lauren A. Sosniak ...[et al.].
This is a great book and suitable for anyone working with children. Similar in nature, but preceeding Stephen Covey's work in 7 Habits of Highly Effective People, this book looks at common traits among talented young people across a multitude of disciplines. The USOC uses this work as a core fundamental in how coaches should work with kids. While this research and book was written in 1985, current research from Carol Dweck, PhD, and author of Mindset, supports the notion that the talent that we see is just a snapshot, a result, of a young persons true talent which is their self-motivated desire. As Bloom states, 100% of young high level performers had, at a young age, a parent, teacher or coach that GAVE them, (not forced on them) a desire for learning or a love of the game. This works in music, math, sports, or anything. You can't get to the top on talent alone! Desire, especially self-motivated desire, which leads to effort is the key! Read it and be transformed in how you work with children!